Zagadnienie optymalnego rozwiązania dla niewypłacalnych spółdzielczych kas oszczędnościowo kredytowych w świetle efektywności dotychczasowych postępowań upadłościowych - Adamus, Rafał Paweł (PRAWO i WIĘŹ, 2025)
This study addresses the problem of the optimal strategy for protecting (a) private interest and (b) public interest in the event of insolvency of a cooperative savings and credit union. According to the available data, the collection of loan claims by trustees of bankrupt credit unions is relatively high. Therefore, the economic effectiveness of bankruptcy proceedings conducted against credit unions in Poland may indicate that it is premature to choose the bankruptcy path.